Guided waves in structures for SHM : the time-domain spectral element method - Ostachowicz, W. M. (Wiesław M.) (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2012)
"Presents the state of the art in the modelling, analysis and experimental investigation of elastic wave propagation using a technique of rapidly increasing interest and development. Addressing an important issue in the field of guided-wave-based damage identification and structural health monitoring, Guided Waves in Structures for SHM presents the modelling, analysis and experimental investigation of elastic wave propagation in engineering structures made of isotropic or composite materials. The authors begin by summarising present-day knowledge on elastic wave propagation in solids, focusing on challenges associated with developing efficient numerical methods and verifying them experimentally. They then progress to describe modelling and analysis using the Spectral Finite Element Method-based approach, presenting the results of numerical tests of elastic wave propagation in structural elements of diverse types ranging from rods through beams, disks, plates and coatings to 3D structures. The section devoted to experimental research describes applications of laser technology for measuring elastic wave propagation in real-life structural elements. Addresses both numerical analysis and experimental research in a single volume. Presents state-of-the-art numerical models based on the Spectral Finite Element Method and experimental research employing laser technologies. Coverage includes an introduction to theory of elastic wave propagation in solids, signal processing techniques the spectral element approach, elastic waves in 1D and 2D structures, EWavePro simulation environment, dispersion relations and damage localisation methods accompanied by a website housing the demo version of the authors' own software dedicated to solve the problems indicated in the book. Original and valuable in its presentation of both numerical analysis and experimental research in a single volume and accompanied by a website housing the demo version of the authors' own software dedicated to solve the problems indicated in the book, Guided Waves in Structures for SHM provides a state of the art resource for researchers, students and practitioners within SHM and NDT."--
Front Matter -- Introduction to the Theory of Elastic Waves -- Spectral Finite Element Method -- Three-Dimensional Laser Vibrometry -- One-Dimensional Structural Elements -- Two-Dimensional Structural Elements -- Three-Dimensional Structural Elements -- Detection, Localisation and Identification of Damage by ElasticWave Propagation -- Appendix: EWavePro Software -- Index.
Includes bibliographical references and index.
Keywords: Elastic analysis (Engineering); Elastic wave propagation -- Mathematical models; Composite materials -- Analysis; Finite element method; SCIENCE -- Mechanics -- General; SCIENCE -- Waves & Wave Mechanics; Electronic books; Electronic books